N-(4-Chlorophenyl)Quinolin-2-Amine - Hasan, Z.A.; Abdullah, Z.; Tajuddin, Hairul Anuar; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
There is a twist in the title molecule, C(15)H(11)ClN(2), as seen in the dihedral angle of 18.85 (9)degrees between the quinoline and benzene rings. A short C-H center dot center dot center dot N contact arises from this conformation and the amine H and quinoline N atoms are directed towards opposite sides of the molecule. In the crystal, supramolecular layers in the ab plane are mediated by C-H center dot center dot center dot pi interactions.